Differentiating clinical care from disease prevention: a prerequisite for practicing quaternary prevention - Charles Dalcanale Tesser; Armando Henrique Norman
Abstract: This article contends that the distinction between clinical care (illness) and prevention of future disease is essential to the practice of quaternary prevention. The authors argue that the ongoing entanglement of clinical care and prevention transforms healthy into "sick" people through changes in disease classification criteria and/or cut-off points for defining high-risk states. This diverts health care resources away from those in need of care and increases the risk of iatrogenic harm in healthy people. The distinction in focus is based on: (a) management of uncertainty (more flexible when caring for ill persons); (b) guarantee of benefit (required only in prevention); (c) harm tolerance (nil or minimal in prevention). This implies attitudinal differences in the decision-making process: greater skepticism, scientism and resistance towards preventive action. These should be based on high-quality scientific evidence of end-outcomes that displays a net positive harm/benefit ratio.